THE EFFECT OF 25% BELT LEAVES AND 0.2% CHLORHEXIDINE AS DISINFECTANT MATERIALS ON THE DIMENSIONAL STABILITY OF ALGINATE MOLDS - Astuti, Ni Kadek Ari; Sumantri; Nasir, Iyan Anugrah (Interdental: Jurnal Kedokteran Gigi, 2021)
Introduction: Dental impression material is one of the agents of infection transmission in the dentist's work environment. Cross infection can occur through the interaction of microorganisms and impression material. To prevent cross infection, it is necessary to disinfect alginate impressions. One of the effective natural ingredients that can be used as a disinfectant is betel leaf. The effect of using disinfectant can affect the dimensional stability of the alginate mold. Purpose: This study aims to determine the effect of disin- fection by spraying a decoction of 25% betel leaf and 0.2% chlorhexidine on the dimensional stability of alginate molds. Materials and Methods: The research method used was an experimental laboratory with a post-test only control group design using 27 samples consisting of three treatments (negative control group, positive control group, and treatment group) which were measured using a digital caliper. The technique used in this study is the spraying technique on the sample with a storage time of 10 minutes. Results and discussion: This 25% betel leaf decoction (infusion) can be used as an alternative to disinfecting alginate impressions because there is no difference in effect between spraying 25% betel leaf decoction (infusion) and 0.2% chlorhexidine on alginate molds on changes in model physiological dimen- sions. Conclusion: the dimensional changes that occur are still within tolera- ble limits in alginate molds which were disinfected by spraying 25% betel leaf decoction and 0.2% chlorhexidine solution so that both can be used as disinfection materials for alginate impression materials.